Kepuasan Konsumen Jasa Tour And Travel CV. Alam Pratama : Ditinjau Dari Customer Experience Dan Kualitas Layanan - Fahimah, Mar'atul; Fahrudin, Jamal (Universitas Indo Global Mandiri, 2023)
The tourism sector has experienced significant changes after the COVID-19 pandemic. The pandemic has had a far-reaching impact on the tourism industry worldwide with travel restrictions, temporary closures of tourist destinations, and changes in consumer behavior. For almost 2 years, the number of visits has increased after it was declared that conditions were gradually returning to normal. This research aims to analyze the influence of customer experience and service quality on consumer satisfaction at travel agencies. CV. Alam Pratama is a company that provides tourism travel agency services, including open trips and tourist services to popular destinations. This research is included in the type of quantitative research. The sampling technique uses purposive sampling. The number of samples in this study was 100 respondents. The analysis technique uses multiple linear regression analysis. The results of the analysis show that partially, customer experience has a positive and significant influence on consumer satisfaction. Likewise, service quality also has a positive and significant influence on consumer satisfaction. Meanwhile, customer experience and service quality simultaneously influence consumer satisfaction at CV. Pratama Nature. Thus, this research emphasizes the importance of paying attention to customer experience and improving service quality in the tourism industry. These findings provide a better understanding of the factors that influence consumer satisfaction, which can help companies develop strategies to improve customer service and experience.